SOSIALISASI PENELITIAN TINDAKAN KELAS BAGI GURU-GURU SMK AL-MAKSUM 2 PULAU KAMPAI - Azrina Purba; Haryati; Putri Ananda; Harry Pratama Figna (LPPM STKIP AL MAKSUM, 2022)
Mastery of Classroom Action Research (CAR) is very important in improving the performance and professionalism of teachers who are responsive to the dynamics of learning. CAR can also improve the learning process and not interfere with the teacher's task in learning at school. For this reason, teachers are required to be able to develop their professionalism, one of which is through Classroom Action Research (CAR). However, teachers often have difficulty in conducting Classroom Action Research (CAR). The limited knowledge of teachers regarding procedures for preparing CAR, strategies, models, learning methods that can be applied in learning, as well as proper data collection, processing, and analysis are obstacles that are often encountered in the field. Therefore, in line with the description above, various efforts are made to improve teacher performance in improving teacher professionalism, namely by holding an activity in the form of socialization to assist teachers in preparing Classroom Action Research (CAR). The results of the service showed that all the socialization materials had been thoroughly explained and the participants were able to understand the material presented. This activity is expected to foster the habit of researching and pouring the results of their research in the form of scientific works to teachers. In addition, teachers have confidence in carrying out their duties and obligations. So that by carrying out classroom action research, teachers can improve the quality of their learning in the classroom.